(3eUHGM GdTQjYI heaJGM GdMbjbIs - (3eLghds
(3ChdgG (B:s
(3GdMeO ddg (B.. (3agPG cJGH (B.. (3ef cdGe GdEeGe GdUGOb (B... (3CHj LYaQ GHf eMeO (B.. (3hjTJed Ydi eGFI HGH hGddg Gdehab ddUhGH , HGH GdChd GdHjGf bGd GdUGOb Ydjg GdSdGe fLhi GdYGQajf JOhQ Ydi KdGKI CUhd (B...s
(3BNQgG (B:s
... (3bh GdbhI GdeJjf aYdeJ Cf hYOg Mb hKhdg UOb aScfJ Edi hYOg hQVjJ Hbhdg hGTJZdJ HeG dg Ydi YeGdg YfOg bGd Ydjg GdSdGe CMSfJ hGddg , GdKeGf bG CQCjJ heG jJcdehfYdi UMI CHOGfge hbheG Ydi cKQI CehGdge (B.. (3JeJs
(3JHUQI GdeDda (B:s
(3eQhjGJ lJfSH dLYaQ GdUGOb QVj Gddg Yfgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI (B21\4167s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdMOjK hGdeUWdMs